DNA methylation analysis of CD4+ T cells in patients with psoriasis - Park, Geon Tae; Han, Jihye; Park, Sin-Gi; Kim, Sangsoo; Kim, Tae-Yoon (Archives of Dermatological Research, 2014)
Psoriasis is a chronic inflammatory skin disease that is characterized by aberrant cross-talk between keratinocytes and immune cells such as CD4+ T cells, resulting in keratinocyte hyperproliferation in the epidermis. DNA methylation, one of several epigenetic mechanisms, plays an important role in gene expression without changing the DNA sequence. Several studies have suggested the involvement of epigenetic regulation in skin lesions from patients with psoriasis. In this study, we investigated the genome-wide DNA methylation status of CD4+ T cells in patients with psoriasis compared with healthy subjects using methylated DNA immunoprecipitation sequencing (MeDIP-Seq). The results of MeDIP-Seq showed that the global methylation values of CD4+ T cells are higher in patients with psoriasis than in healthy controls, particularly in the promoter regions. Among the most hypermethylated genes in the promoter regions, we selected the genes whose expression is significantly reduced in the CD4+ T cells of psoriasis patients. Studies using the methylation inhibitor 5-azacytidine in vitro methylation assays have shown that the differential expression levels were associated with the methylation status of each gene. Bisulfite sequencing of the transcription start region of phosphatidic acid phosphatase type 2 domain containing 3 ( PPAPDC3 ), one of the selected genes, showed hypermethylation in the CD4+ T cells of psoriasis patients. These results suggested that the methylation status, which is identified by MeDIP-Seq of the genes, was correlated with the mRNA expression level of the genes. Collectively, the DNA methylation status in CD4+ T cells might be associated with the pathogenesis of psoriasis.